Novel sodium iron silicate sulfate composite polyanion positive electrode material for sodium-ion battery and preparation method of novel sodium iron silicate sulfate composite polyanion positive electrode material
By introducing silicate into sulfate polyanionic materials, a new type of iron sodium silicate composite polyanionic cathode material was designed, which solved the problem of easy decomposition of the material and difficulty in electron transport at high temperatures, and achieved improvement of the structural stability and electrochemical performance of the material.
Patent Information
- Application Number
- CN202510060810.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Sulfate polyanionic materials are easy to decompose at high temperatures, and electron transport is difficult, resulting in insufficient capacity and rapid attenuation, and it is difficult to achieve uniform mixing of Na, Fe, S and O elements, affecting electrochemical performance.
By introducing silicate, a new composite polyanionic cathode material of sodium ferrosilicate sulfate is designed, and spray-drying and sintering processes are adopted to improve the structural stability and electrochemical properties of the material, and in-situ coated biomass carbon is achieved.
It significantly improves the thermodynamic stability of the material, prevents the decomposition of sulfate, enhances electronic conductivity, reduces production costs, and improves the performance and cycle stability of sodium ion batteries.
Smart Images

Figure CN119695149A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel sodium ferric sulfate silicate composite polyanion positive electrode material for a sodium ion battery and a preparation method thereof, belonging to the technical field of sodium ion batteries. Background Art
[0002] With the growing global energy demand and increasingly severe environmental problems, the development of new and efficient energy storage systems has become particularly important. As the most mainstream secondary battery technology, lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and large-scale energy storage systems due to their high energy density and long cycle life. However, the uneven geographical distribution of lithium resources and cost issues limit their feasibility in large-scale applications. Therefore, the development of new sodium-ion batteries as an alternative technology has received widespread attention. Sodium-ion batteries have similar working principles to lithium-ion batteries, but sodium resources are more abundant and low-cost, which makes sodium-ion batteries have potential advantages in the field of large-scale energy storage.
[0003] In the research and development of sodium-ion batteries, polyanion cathode materials have attracted much attention due to their unique structural advantages and excellent electrochemical properties. In particular, sulfate polyanion materials, such as Alluaudite-type Na2Fe2(SO4)3 and Eldfellite-type NaFe(SO4)2, are considered to be highly promising sodium-ion battery cathode materials due to their high operating voltage, long cycle life and low cost. However, there are some urgent problems to be solved in the practical application of such materials. First, sulfate cathode materials are prone to sulfate decomposition at high temperatures to produce SO x Gas, this characteristic limits its possibility of carbon coating modification through traditional high-temperature pyrolysis process. Furthermore, since FeO6 is connected by non-conductive SO4 groups, it is difficult for electrons to be transmitted during the charge and discharge process, resulting in insufficient capacity and rapid capacity decay of the original material at high rates. In addition, solid-phase ball milling and low-temperature sintering technology make it difficult to achieve uniform mixing of Na, Fe, S and O elements at the molecular level, resulting in difficulty in the diffusion of element concentrations during low-temperature sintering, and easy production of impurities such as Fe3O4 or Na6Fe(SO4)4, which affects the electrochemical properties of the material. Finally, although the finished conductive material can be added to an aqueous solution containing sodium sulfate and ferrous sulfate for ultrasonic dispersion and then sintered at low temperature to obtain a composite positive electrode material with improved electronic conductivity, since the conductive carbon material is generally a nano-scale hydrophobic material, it is very easy to agglomerate. Simple ultrasonic dispersion is difficult to make it completely and evenly dispersed in the aqueous solution, resulting in uneven conductivity distribution in the prepared composite positive electrode material particles, affecting the high-rate performance and cycle stability of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion batteries and a preparation method thereof. By introducing a silicate component, a novel sodium ferric sulfate silicate composite polyanion positive electrode material is designed to improve the structural stability and electrochemical performance of the material, thereby solving the problem that sulfate polyanion materials cannot be thermally decomposed in situ to coat biomass conductive carbon, and further confirming its electrochemical activity and potential application value.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A sodium ion battery prepared from a novel sodium ferric sulfate silicate composite polyanion positive electrode material comprises the following steps:
[0007] (1) A sodium source, an iron source, a silicon source, a sulfate, an antioxidant and / or a carbon source are added to deionized water, and the mixture is continuously stirred to be uniformly dispersed to obtain a yellow suspension, and the suspension is spray-dried to obtain a composite precursor powder.
[0008] (2) The composite precursor is sintered in a tubular furnace with an inert atmosphere and then cooled to room temperature to obtain a sodium iron silicate sulfate composite positive electrode material.
[0009] (3) The positive electrode material, conductive carbon black and binder were weighed in a mass fraction ratio of 70:20:10 and dry-grinded in an agate mortar for 20 to 30 minutes. The solvent NMP was added and wet-grinded for 30 minutes to obtain a black slurry with good fluidity. The black slurry was evenly coated on aluminum foil, dried in a vacuum oven at 100°C for 8 hours, and then cut into circular positive electrode sheets using a cutting machine. The sodium ion battery was assembled in a glove box filled with Ar (water and oxygen contents were both less than 0.1ppm).
[0010] Furthermore, in step (1), the sodium source is sodium sulfate, the iron source is ferrous oxalate or ferrous sulfate, and the silicon source is silicon dioxide.
[0011] Furthermore, in step (1), the molar ratio of sodium sulfate to silicon dioxide is 1 to 2:1, the molar ratio of ferrous sulfate to silicon dioxide is 0 to 2:1, and the molar ratio of ferrous oxalate to silicon dioxide is 1 to 2:1. The chemical formula of the prepared positive electrode material is Na2Fe2(SiO4): x (SO4) y (0.05≤x≤1,1≤y≤2).
[0012] Furthermore, in step (1), the antioxidant may be citric acid or ascorbic acid, and the molar ratio of citric acid to ferrous oxalate heptahydrate is 1:10.
[0013] Furthermore, in step (1), the carbon source accounts for 0-5% of the mass of sodium ferric silicate sulfate, and the carbon source can be glucose, sucrose or maltose.
[0014] Furthermore, in step (1), the spray drying temperature is 150-200°C.
[0015] Furthermore, in step (1), the inert atmosphere is Ar or N2.
[0016] Furthermore, in step (2), the calcination temperature is 350-700° C., and the calcination time is 8-12 hours.
[0017] Beneficial Effects
[0018] The present invention discloses a novel sulfate silicate Na2Fe2(SiO4) x (SO4) y (0.05≤x≤1,1≤y≤2) sodium ion battery positive electrode material, the material preparation process adopts a simple spray drying combined with sintering process, and through the innovative introduction of silicate, a new sodium ferric sulfate silicate composite polyanion positive electrode material is designed, which significantly improves the thermodynamic stability of the material, effectively prevents the decomposition of sulfate during high-temperature synthesis, and can in-situ coat low-cost biomass carbon at high temperature, which not only reduces the production cost, but also enhances the electronic conductivity of the material. The initial discharge specific capacity of Na2Fe2SiO4SO4 / C-700 at 0.05C is 57.79mAh / g. The present invention not only solves the stability problem of traditional sulfate materials at high temperatures, but also provides a new solution for improving the performance and reducing the cost of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0020] Figure 1 This is the SEM image of the Na2Fe2SiO4SO4 / C-700 material in Example 1.
[0021] Figure 2 This is the XRD diagram of the Na2Fe2SiO4SO4 / C-700 material in Example 1.
[0022] Figure 3 It is Na2Fe2(SiO4) prepared in Example 11 0.5 SEM image of (SO4)2 / C-700 material.
[0023] Figure 4 It is Na2Fe2(SiO4) prepared in Example 11 0.5XRD pattern of (SO4)2 / C-700 material.
[0024] Figure 5 This is the 0.05C first constant current charge and discharge performance of the Na2Fe2SiO4SO4 / C-700 positive electrode material in Example 1.
[0025] Figure 6 This is the rate performance test of the Na2Fe2SiO4SO4 / C-700 positive electrode material in Example 1. DETAILED DESCRIPTION
[0026] The present invention will be further described in detail below in conjunction with specific embodiments.
[0027] Example 1
[0028] Preparation of Na2FeSiO4SO4 / C-700 material:
[0029] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid and 5wt% glucose were added in a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide was obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide was dried in a spray dryer at 200°C to obtain a yellow solid powder, which was then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder was sintered at 700°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4 / C-700 composite positive electrode material.
[0030] The Na2FeSiO4SO4 / C-700 positive electrode material prepared in Example 1 of the present invention was mixed with a conductive agent and a binder in a ratio of 70:20:10 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C~0.5C (1C=135mA / g).
[0031] Figure 1 This is the SEM image of the Na2FeSiO4SO4 / C-700 material prepared in Example 1. The composite material has an irregular block morphology.
[0032] Figure 2 The XRD diagram of the Na2FeSiO4SO4 / C-700 material prepared in Example 1 shows that the material has good crystallinity.
[0033] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 1 at 0.05C is 57.79 mAh / g.
[0034] Example 2
[0035] Preparation of Na2FeSiO4SO4 / C-600 material:
[0036] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid and 5wt% glucose were added in a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide was obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide was dried in a spray dryer at 200°C to obtain a yellow solid powder, and then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder was sintered at 600°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4 / C-600 composite positive electrode material.
[0037] The Na2FeSiO4SO4 / C-600 positive electrode material prepared in Example 2 of the present invention was mixed with a conductive agent and a binder in a ratio of 70:20:10 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0038] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 2 at 0.05C is 46.05 mAh / g.
[0039] Example 3
[0040] Preparation of Na2FeSiO4SO4 / C-500 material:
[0041] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid and 5wt% glucose were added in a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide was obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide was dried at 200°C in a spray dryer to obtain a yellow solid powder, which was then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder was sintered at 500°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4 / C-500 composite positive electrode material.
[0042] The Na2FeSiO4SO4 / C-500 positive electrode material prepared in Example 3 of the present invention was mixed with a conductive agent and a binder in a ratio of 70:20:10 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0043] The electrochemical performance of the assembled battery is shown in Table 1. It can be seen from the table that the first discharge capacity of Example 3 at 0.05C is 36.62 mAh / g.
[0044] Example 4
[0045] Preparation of Na2FeSiO4SO4-700 material:
[0046] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried at 200°C in a spray dryer to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 700°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-700 composite positive electrode material.
[0047] The Na2FeSiO4SO4-700 positive electrode material prepared in Example 4 of the present invention was mixed with a conductive agent and a binder in a ratio of 70:20:10 to form a uniform slurry; then, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0048] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 4 at 0.05C is 45.44 mAh / g.
[0049] Example 5
[0050] Preparation of Na2FeSiO4SO4-600 material:
[0051] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried at 200°C in a spray dryer to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 600°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-600 composite positive electrode material.
[0052] The Na2FeSiO4SO4-600 positive electrode material prepared in Example 5 of the present invention was mixed with a conductive agent and a binder in a ratio of 70:20:10 to form a uniform slurry; then, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05 (1C=135mA / g).
[0053] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 5 at 0.05C is 33.70 mAh / g.
[0054] Example 6
[0055] Preparation of Na2FeSiO4SO4-550 material:
[0056] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried at 200°C in a spray dryer to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 550°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-550 composite positive electrode material.
[0057] The Na2FeSiO4SO4-550 positive electrode material prepared in Example 6 of the present invention was mixed with a conductive agent and a binder in a ratio of 40:40:20 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0058] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 6 at 0.05C is 25.62 mAh / g.
[0059] Example 7
[0060] Preparation of Na2FeSiO4SO4-500 material:
[0061] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried at 200°C in a spray dryer to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 500°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-500 composite positive electrode material.
[0062] The Na2FeSiO4SO4-500 positive electrode material prepared in Example 7 of the present invention was mixed with a conductive agent and a binder in a ratio of 40:40:20 to form a uniform slurry; then, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0063] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 7 at 0.05C is 80.06 mAh / g.
[0064] Example 8
[0065] Preparation of Na2FeSiO4SO4-450 material:
[0066] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried in a spray dryer at 200°C to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 450°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-450 composite positive electrode material.
[0067] The Na2FeSiO4SO4-450 positive electrode material prepared in Example 8 of the present invention was mixed with a conductive agent and a binder in a ratio of 40:40:20 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0068] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 8 at 0.05C is 97.12 mAh / g.
[0069] Example 9
[0070] Preparation of Na2FeSiO4SO4-400 material:
[0071] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried in a spray dryer at 200°C to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 400°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-400 composite positive electrode material.
[0072] The Na2FeSiO4SO4-400 positive electrode material prepared in Example 9 of the present invention was mixed with a conductive agent and a binder in a ratio of 40:40:20 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0073] The electrochemical performance of the assembled battery is shown in Table 1, from which it can be seen that the first discharge capacity of Example 9 at 0.05C is 157.73 mAh / g. The discharge capacity of Example 9 at 0.05C exceeds the theoretical specific capacity, which may be due to the decomposition of the electrolyte.
[0074] Example 10
[0075] Preparation of Na2FeSiO4SO4-350 material:
[0076] Sodium sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 1:2:1 and added to deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ An appropriate amount of citric acid is added at a molar ratio of 10:1, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous oxalate and silicon dioxide is dried at 200°C in a spray dryer to obtain a yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 350°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain a Na2FeSiO4SO4-350 composite positive electrode material.
[0077] The Na2FeSiO4SO4-350 positive electrode material prepared in Example 10 of the present invention was mixed with a conductive agent and a binder in a ratio of 40:40:20 to form a uniform slurry; subsequently, the obtained black slurry was coated on an aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10 hours to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1 cm by a cutting machine, a sodium sheet was used as a negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolytes, and glass fiber was used as a diaphragm to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=135mA / g).
[0078] The electrochemical performance of the assembled battery is shown in Table 1, from which it can be seen that the first discharge capacity of Example 10 at 0.05C is 273.29 mAh / g. The discharge capacity of Example 10 at 0.05C exceeds the theoretical specific capacity, which may be due to the decomposition of the electrolyte.
[0079] Embodiment 11
[0080] Preparation of Na2Fe2(SiO4) 0.5 (SO4)2 / C-700 Materials:
[0081] Sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 2:2:2:1 and added into deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ The molar ratio is 10:1. An appropriate amount of citric acid and 5wt% glucose are added, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is dried in a spray dryer at 200°C to obtain a light yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 700°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain Na2Fe2(SiO4) 0.5 (SO4)2 / C-700 positive electrode material.
[0082] The Na2Fe2(SiO4) prepared in Example 11 of the present invention 0.5 (SO4)2 / C-700 positive electrode material was mixed with conductive agent and binder in a ratio of 70:20:10 to form a uniform slurry; then, the obtained black slurry was coated on aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10h to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1cm by a cutting machine, sodium sheet was used as negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolyte, and glass fiber was used as a separator to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=120mA / g).
[0083] Figure 3 Preparation of Na2Fe2(SiO4) for Example 11 0.5 SEM image of (SO4)2 / C-700 material, the material has a micron-scale block structure.
[0084] Figure 4 Preparation of Na2Fe2(SiO4) for Example 11 0.5 XRD diagram of (SO4)2 / C-700 material, the material has good crystallinity.
[0085] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 11 at 0.05C is 44.18 mAh / g.
[0086] Example 12
[0087] Preparation of Na2Fe2(SiO4) 0.5 (SO4)2 / C-600 Materials:
[0088] Sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 2:2:2:1 and added into deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ The molar ratio is 10:1. An appropriate amount of citric acid and 5wt% glucose are added, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is dried in a spray dryer at 200°C to obtain a light yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 600°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain Na2Fe2(SiO4) 0.5 (SO4)2 / C-600 positive electrode material.
[0089] The Na2Fe2(SiO4) prepared in Example 12 of the present invention 0.5 (SO4)2 / C-600 positive electrode material was mixed with conductive agent and binder in a ratio of 70:20:10 to form a uniform slurry; then, the obtained black slurry was coated on aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10h to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1cm by a cutting machine, sodium sheet was used as negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolyte, and glass fiber was used as a separator to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=120mA / g).
[0090] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 12 at 0.05C is 32.44 mAh / g.
[0091] Embodiment 13
[0092] Preparation of Na2Fe2(SiO4) 0.5 (SO4)2 / C-500 Materials:
[0093] Sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 2:2:2:1 and added into deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+The molar ratio is 10:1. An appropriate amount of citric acid and 5wt% glucose are added, and then a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is obtained. The mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is dried in a spray dryer at 200°C to obtain a light yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 500°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain Na2Fe2(SiO4) 0.5 (SO4)2 / C-500 positive electrode material.
[0094] The Na2Fe2(SiO4) prepared in Example 13 of the present invention 0.5 (SO4)2 / C-500 positive electrode material was mixed with conductive agent and binder in a ratio of 70:20:10 to form a uniform slurry; then, the obtained black slurry was coated on aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10h to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1cm by a cutting machine, sodium sheet was used as negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolyte, and glass fiber was used as a separator to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C (1C=120mA / g).
[0095] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 13 at 0.05C is 23.01 mAh / g.
[0096] Embodiment 14
[0097] Preparation of Na2Fe2(SiO4) 0.5 (SO4)2-700 Material:
[0098] Sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide were weighed in a molar ratio of 2:2:2:1 and added into deionized water. Stir continuously for 2 to 3 hours. During this time, citric acid:Fe 2+ The molar ratio is 10:1, and an appropriate amount of citric acid is added to obtain a yellow and uniformly dispersed mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide. The mixed suspension of sodium sulfate, ferrous sulfate, ferrous oxalate and silicon dioxide is dried in a spray dryer at 200°C to obtain a light yellow solid powder, which is then vacuum dried in a vacuum oven at 100°C for 10 hours to obtain a precursor powder. The precursor powder is sintered at 700°C in a tubular furnace with an Ar atmosphere for 10 hours and then cooled to room temperature to obtain Na2Fe2(SiO4) 0.5(SO4)2-700 positive electrode material.
[0099] The Na2Fe2(SiO4) prepared in Example 14 of the present invention 0.5 (SO4)2-700 positive electrode material was mixed with conductive agent and binder in a ratio of 70:20:10 to form a uniform slurry; then, the obtained black slurry was coated on aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10h to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1cm by a cutting machine, sodium sheet was used as negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolyte, and glass fiber was used as a separator to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.05C~0.5C (1C=120mA / g).
[0100] The electrochemical properties of the assembled battery are shown in Table 1. It can be seen from the table that the first discharge capacity of Example 14 at 0.05C is 21.03 mAh / g.
[0101] Comparative Example 1
[0102] Preparation of Na 2+2x Fe 2-x (SO4)3 Material:
[0103] Dissolve Na2SO4 and FeSO4·7H2O in 25 ml of deionized water at a molar ratio of 1:1, and stir continuously until dissolved. Add appropriate amounts of ascorbic acid and glucose during the process, and stir thoroughly for 10 minutes to obtain a clear solution. Add the mixed solution dropwise into 100 ml of ethanol solution to obtain a gray-green precipitate. Wash the precipitate with alcohol and filter it, and dry it at 60°C for 12 hours to obtain a precursor powder. Calcinate the precursor powder at 350°C in an Ar atmosphere for 2 hours to obtain the product Na 2+ 2x Fe 2-x (SO4)3.
[0104] The Na prepared in Comparative Example 1 of the present invention 2+2x Fe 2-x(SO4)3 positive electrode material, conductive agent and binder were mixed into a uniform slurry in a ratio of 70:20:10; then, the obtained black slurry was coated on aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10h to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1cm by a cutting machine, sodium sheet was used as negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolyte, and glass fiber was used as a separator to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.1C (1C=100mA / g).
[0105] The electrochemical performance of the battery assembled in Comparative Example 1 is 22.5 mAh / g at a discharge capacity of 0.1C.
[0106] Comparative Example 2
[0107] Preparation of Na 2+2x Fe 2-x (SO4)3 Material:
[0108] Dissolve Na2SO4 and FeSO4·7H2O in 25 ml of deionized water at a molar ratio of 1:2, and stir continuously until dissolved. Add appropriate amounts of ascorbic acid and glucose during the process, and stir thoroughly for 10 minutes to obtain a clear solution. Add the mixed solution dropwise into 100 ml of ethanol solution to obtain a gray-green precipitate. Wash the precipitate with alcohol and filter it, and dry it at 60°C for 12 hours to obtain a precursor powder. Calcinate the precursor powder at 350°C in an Ar atmosphere for 2 hours to obtain the product Na 2+ 2x Fe 2-x (SO4)3.
[0109] The Na prepared in Comparative Example 2 of the present invention 2+2x Fe 2-x (SO4)3 positive electrode material, conductive agent and binder were mixed into a uniform slurry in a ratio of 70:20:10; then, the obtained black slurry was coated on aluminum foil with a scraper and dried in a vacuum oven at 100°C for 10h to obtain a working electrode; then, the obtained working electrode was cut into a circular positive electrode sheet with a diameter of 1.1cm by a cutting machine, sodium sheet was used as negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol% FEC were used as electrolyte, and glass fiber was used as a separator to prepare a button battery. The electrochemical performance test was completed under the monitoring of the Neware system, with a test voltage range of 1.5~4.5V, a test temperature of 30°C, and a current density of 0.1C (1C=100mA / g).
[0110] The electrochemical performance of the battery assembled in Comparative Example 2 is 21.0 mAh / g at a discharge capacity of 0.1C.
[0111] Table 1 shows the electrochemical performance test results of the half-cell of the embodiment. It can be seen that carbon coating improves the first cycle discharge capacity of the material, which further proves that the introduction of silicate can improve the thermodynamic stability of sulfate, enabling it to be in-situ coated with biochar at high temperature. + The ion transfer rate is increased, resulting in a higher discharge specific capacity. The overall performance of Na2FeSiO4SO4 material is better than that of Na2Fe2(SiO4) 0.5 (SO4)2 is more stable, probably due to its superior crystal structure and Na + Diffusion channel.
[0112] Table 1 Half-cell electrochemical performance test results
[0113]
[0114]
[0115] from Figure 5 It can be seen that the initial discharge capacity of the sodium ion battery prepared in Example 1 is 57.79 mAh / g at a current density of 0.05 C, indicating that the Na2FeSiO4SO4 / C-700 composite cathode material can indeed achieve Na + reversible deintercalation.
[0116] from Figure 6 It can be seen that the sodium ion battery prepared in Example 1 has a decent discharge capacity at current densities of 0.05C, 0.1C, and 0.2C, but has a poor discharge capacity at higher current densities, such as 0.5C, 1.0C, and 2.0C. The inherent low electronic conductivity of the polyanionic material limits the capacity at high rates.
[0117] Combination Figure 5 and Figure 6 It can be inferred that the Na2FeSiO4SO4 / C material cannot fully exert its discharge specific capacity due to the intrinsic low electronic conductivity of the polyanion, and further hierarchical structure or nano-sizing strategy is needed to improve its energy storage performance.
[0118] The embodiments listed above are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Those skilled in the art should understand that the present invention may be changed and improved without departing from the scope of the present invention.
Claims
1. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion batteries and a preparation method thereof, characterized in that: The novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion batteries is prepared by the following steps: (1) A sodium source, an iron source, a silicon source, a sulfate, an antioxidant and / or a carbon source are added to deionized water, and the mixture is continuously stirred to be uniformly dispersed to obtain a yellow suspension, and the suspension is spray-dried to obtain a composite precursor powder. (2) The composite precursor is sintered in a tube furnace with an inert atmosphere and then cooled to room temperature to obtain Na2Fe2(SiO4) x (SO4) y Sodium ferric sulfate silicate composite cathode material and / or carbon-coated Na2Fe2(SiO4) x (SO4) y / C positive electrode material.
2. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The sodium ion battery is prepared by the following steps: The positive electrode material, conductive carbon black and binder were weighed in a mass fraction ratio of 70:20:10 in an agate mortar and dry-grinded for 20 to 30 minutes. After adding the solvent NMP and wet-grinding for 30 minutes, a black slurry with good fluidity was obtained. The black slurry was evenly coated on aluminum foil and dried in a vacuum oven at 100°C for 8 hours, and then cut into circular positive electrode sheets using a cutting machine. The sodium ion battery was assembled in a glove box filled with Ar (water and oxygen contents were both less than 0.1ppm).
3. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The sodium source is sodium sulfate, the iron source is ferrous oxalate or ferrous sulfate, and the silicon source is silicon dioxide.
4. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The molar ratio of sodium sulfate to silicon dioxide is 1 to 2:1, the molar ratio of ferrous sulfate to silicon dioxide is 0 to 2:1, and the molar ratio of ferrous oxalate to silicon dioxide is 1 to 2:
1. The chemical formula of the prepared positive electrode material is Na2Fe2(SiO4) x (SO4) y (0.05≤x≤1,1≤y≤2).
5. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The antioxidant may be citric acid or ascorbic acid, and the molar ratio of citric acid to ferrous oxalate heptahydrate is 1:
10.
6. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The carbon source accounts for 0-5% of the mass of sodium ferric sulfate silicate, and the carbon source can be glucose, sucrose or maltose.
7. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The spray drying temperature is 150-200°C.
8. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion battery and a preparation method thereof according to claim 1, characterized in that: The inert atmosphere is Ar or N2.
9. A novel sodium ferric sulfate silicate composite polyanion positive electrode material for sodium ion batteries and a preparation method thereof according to claim 1, characterized in that: The calcination temperature is 350-700° C., and the calcination time is 8-12 hours.
Citation Information
Patent Citations
Molybdenum-ytterbium co-doped sodium iron silicate composite electrode material, and preparation method and application thereof
CN109638274A
Na2Fe(SO4)2 / C electrode material jointly prepared by graphene and / or acetylene black, preparation method thereof and prepared battery
CN110336021A
Preparation method of Na2Fe (SO4) 2 / C as sodium ion battery composite positive electrode material
CN115159581A
In-situ carbon-coated sodium ferrous sulfate composite positive electrode material, preparation and sodium ion battery
CN116354405A
Composite polyanionic sodium ferrous sulfate positive electrode material and preparation method thereof, and sodium ion battery containing positive electrode material
CN116960281A